Community socioeconomic deprivation and obesity trajectories in children using electronic health records. (16th October 2014) - Nau, Claudia; Schwartz, Brian S.; Bandeen‐Roche, Karen; Liu, Anne; Pollak, Jonathan; Hirsch, Annemarie; Bailey‐Davis, Lisa; Glass, Thomas A.
<x xml:space="preserve">Abstract</x> Objectives Longitudinal studies of the role of community context in childhood obesity are lacking. The objective of this study was to examine associations of community socio economic deprivation (CSD) with trajectories of change in body mass index (BMI) in childhood and adolescence. Methods Data came from electronic health records on 163, 473 children aged 3‐18 residing in 1, 288 communities in Pennsylvania whose weight and height were measured longitudinally. CSD at the year of birth was measured using six US Census variables and modeled in quartiles. Trajectories of BMI within CSD quartiles were estimated using random effects growth‐curve models accounting for differences by age, sex, and race/ethnicity as well as correcting for non‐constant residual variance across age groups. Results CSD was associated with higher BMI at average age (10.7 years) and with more rapid growth of BMI over time. Children born in communities with greater CSD had steeper increases of BMI at younger ages. Those born into the poorest communities displayed sustained accelerated BMI growth. CSD remained associated with BMI trajectories after adjustment for a measure of household socio economic deprivation. Conclusions Higher CSD may be associated with more obesogenic growth trajectories in early life. Findings suggest that individual‐level interventions that ignore the effect of community context on obesity‐related behaviors may be less efficient.